Health Education Through The “Lawan TBC” Movement to Improve Tuberculosis Prevention Knowledge in Islamic Boarding Schools - Marinda Dwi Puspitarini; Kartuti Debora; Aldilia Wyasti Pratama; Yuriske Agnovianto; Diana Arum Lisnawati; Muhammad Hefdi; Clarissa Septianingrum (Al-Qalam Institute, 2026)
Tuberculosis (TB) remains a major public health concern in Islamic boarding schools due to the high risk of disease transmission in communal living environments. This study aimed to evaluate the effectiveness of the